Metal-organic and covalent-organic frameworks for CO2 capture - Rana, Supriyanka; Sharma, Eshita; Mishra, Puranjan; Singh, Lakhveer; Zularisam, Ab Wahid; Reena, Gupta L.; Sharma, Swati (Elsevier, 2023)
The relentless search for more efficient novel material frameworks for carbon capture application is mutual among both academia and industry. The high CO2 separation selectivity of materials such as metal-organic framework (MOF) and covalent-organic framework (COF) is established worldwide due to their excellent structural properties like large surface areas, high tunable porosity, functionalities, and stability. Futuristic requisite of competitive materials for CO2 capture enhancement has been met with hybrid structure innovation (MOF–COF hybrids) constituted by amalgamating the best of MOF and COF characteristics into one. Encouraging excellent CO2 separability of hybrid structural frameworks has advocated for its applications in other diverse fields that could be benefitted from synergy between MOFs and COFs. This chapter will provide the recent state of art in the field of major CO2 capturing materials, mainly MOFs, COFs, and their hybrids. Innovation of next-generation nano-powered design strategies is capable of surpassing current challenges of existing material types, the only way forward to realize our goal of creating a clean and sustainable world.